Pharmacokinetics of evocalcet in secondary hyperparathyroidism patients receiving hemodialysis: first-in-patient clinical trial in Japan - Shigematsu T; Shimazaki R; Fukagawa M; Akizawa T (Dove Medical Press, 2018)
Takashi Shigematsu,1 Ryutaro Shimazaki,2 Masafumi Fukagawa,3 Tadao Akizawa4 On behalf of the Evocalcet Study Group 1Department of Nephrology, Wakayama Medical University, Wakayama, Japan; 2R&D Division, Kyowa Hakko Kirin Co., Ltd., Chiyoda-ku, Tokyo, Japan; 3Department of Internal Medicine, Division of Nephrology, Endocrinology and Metabolism, Tokai University School of Medicine, Isehara, Kanagawa, Japan; 4Department of Medicine, Division of Nephrology, Showa University School of Medicine, Minato-ku, Tokyo, Japan Purpose: Cinacalcet is a positive allosteric modulator of calcium-sensing receptors in the parathyroid gland and an effective treatment for secondary hyperparathyroidism. However, this agent has considerable side effects and dosage limitations, which impair effective treatment. Therefore, we investigated the pharmacokinetics, pharmacodynamics, and safety of the novel calcimimetic, evocalcet.Patients and methods: This was a multicenter, open-label study of single oral doses of 1, 4, and 12 mg evocalcet using an intrapatient dose escalation protocol in 29 Japanese secondary hyperparathyroidism patients receiving hemodialysis. Pharmacokinetics was assessed by plasma evocalcet concentrations. Pharmacodynamic evaluations consisted of measuring intact parathyroid hormone, serum corrected calcium, and fibroblast growth factor 23 concentrations. Safety and tolerability were evaluated by the analysis of adverse events (AEs).Results: After a single 1-, 4-, or 12-mg dose, plasma evocalcet levels increased dose proportionally in a linear manner. Pharmacodynamic analyses showed that evocalcet effectively reduced intact parathyroid hormone and serum corrected calcium levels in a dose-dependent manner. AEs occurred in 31.0%, 28.6%, and 38.5% of patients receiving a single dose of 1, 4, or 12 mg, respectively. Most AEs were mild in severity.Conclusion: Evocalcet is effective in the short term, has linear pharmacokinetics, and is well tolerated as observed by the low incidence of AEs. Keywords: Calcimimetics, evocalcet, hemodialysis, parathyroid hormone, secondary hyperparathyroidism